Tumor-associated macrophages (TAMs): Constructing an immunosuppressive microenvironment bridge for pancreatic ductal adenocarcinoma (PDAC) - Liu, Runjie; Li, Jianang; Liu, Liang; Wang, Wenquan; Jia, Jinbin (Cancer pathogenesis and therapy, 2025)
Pancreatic ductal adenocarcinoma (PDAC) is a fatal disease with increasing incidences worldwide. The overall 5-year survival rate remains low, underscoring the urgent need for effective therapies. Despite the promising efficacy of immunotherapy for various solid tumors, its benefits for pancreatic cancer have been disappointing. This is largely because of the complex and unique mechanisms of immune evasion inherent in PDAC. Emerging evidence has highlighted the pivotal role of tumor-associated macrophages (TAMs) in facilitating the immune escape of PDAC. TAMs significantly contribute to forming an immunosuppressive microenvironment, which hinders the effectiveness of immunotherapeutic approaches. They achieve this through multiple pathways, including the secretion of cytokines and the promotion or inhibition of multiple immune cells. In this review, we summarized the main pathways through which TAMs form an immunosuppressive microenvironment in PDAC. We also examined the current status and recent progress of immunotherapy strategies that specifically target macrophages. By understanding these mechanisms and exploring targeted therapies, we aimed to shed light on potential avenues for improving the treatment outcomes of this devastating disease. [Display omitted] •Tumor-associated macrophages (TAMs) have the ability to promote and inhibit pancreatic ductal adenocarcinoma (PDAC).•Crosstalk between TAMs and immune cells is the key to an immunosuppressive microenvironment.•Targeting TAMs for reverse immunosuppression is a future direction of PDAC treatment.